Implementation of Domes Building in Simoketawang Village Tourism Education Facilities, Sidoarjo City - Windy Fitria Kermatigo; Febby Rahmatullah Masruchin (Pelopor Publikasi Akademika, 2023)
The application of dome buildings in tourist education facilities in Simoketawang Village, Sidoarjo aims to increase educational value and attract tourists to visit the village. In this discussion, we explore the benefits and potential of applying dome structures in the context of educational tourism in Simoketawang Village. Through literature recognition, we found that the application of dome structures, such as geodesic domes, ellipsoid domes, and tropical domes, can provide architectural uniqueness and interesting experiences for visitors. Geodesic domes, with triangular segment structures, provide robustness and efficiency in construction, while ellipsoids of domes give a dynamic and aesthetic impression of modernity. The tropical dome, with its hollow and open design, prioritizes air circulation and natural lighting. In addition, the discussion also involved aspects of sustainability and community participation in the development of village tourism. The application of domes in tourist education facilities can support sustainable design principles, such as the use of natural materials and optimization of natural resources. In addition, the participation of local communities is also important in the preservation of cultural heritage and the development of ecotourism in Simoketawang Village.By combining unique architectural designs, educational values, and launches, the application of domes buildings in Simoketawang Village can provide a unique and interesting tourist experience for visitors, while supporting the development of ecotourism and the preservation of local culture.